Chest Pain and Costochondritis Associated with Vitamin D Deficiency: A Report of Two Cases - Robert C. Oh; Jeremy D. Johnson (Case Reports in Medicine)
Vitamin D is integral for bone health, and severe deficiency can cause rickets in children and osteomalacia in adults. Although osteomalacia can cause severe generalized bone pain, there are only a few case reports of chest pain associated with vitamin D deficiency. We describe 2 patients with chest pain that were initially worked up for cardiac etiologies but were eventually diagnosed with costochondritis and vitamin D deficiency. Vitamin D deficiency is known to cause hypertrophic costochondral junctions in children (“rachitic rosaries”) and sternal pain with adults diagnosed with osteomalacia. We propose that vitamin D deficiency may be related to the chest pain associated with costochondritis. In patients diagnosed with costochondritis, physicians should consider testing and treating for vitamin D deficiency.